2012
DOI: 10.1103/physrevlett.108.106602
|View full text |Cite
|
Sign up to set email alerts
|

Local Charge and Spin Currents in Magnetothermal Landscapes

Abstract: A scannable laser beam is used to generate local thermal gradients in metallic (Co2FeAl) or insulating (Y3Fe5O12) ferromagnetic thin films. We study the resulting local charge and spin currents that arise due to the anomalous Nernst effect (ANE) and the spin Seebeck effect (SSE), respectively. In the local ANE experiments, we detect the voltage in the Co2FeAl thin film plane as a function of the laser-spot position and external magnetic field magnitude and orientation. The local SSE effect is detected in a sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
236
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(252 citation statements)
references
References 35 publications
16
236
0
Order By: Relevance
“…Thus, the angle dependence of V perfectly corresponds to the crossproduct of Eq. (1) contribution for α = 0 • could be the magnetic anisotropy of the NiFe 2 O 4 films as was also demonstrated for YIG films 14 . Therefore, measurements using vibrating sample magnetometry (VSM) are performed and presented in Fig.…”
Section: Fig 2 (A) Andmentioning
confidence: 78%
“…Thus, the angle dependence of V perfectly corresponds to the crossproduct of Eq. (1) contribution for α = 0 • could be the magnetic anisotropy of the NiFe 2 O 4 films as was also demonstrated for YIG films 14 . Therefore, measurements using vibrating sample magnetometry (VSM) are performed and presented in Fig.…”
Section: Fig 2 (A) Andmentioning
confidence: 78%
“…[3][4][5] For the opposite effect, to use Pt as a spin current injector, a charge current is sent through the Pt, creating a transverse spin accumulation by the spin-Hall effect (SHE). [6][7][8] Recently, Weiler et al 9 and Huang et al 10 observed magnetoresistance (MR) effects in Pt on YIG and related those effects to magnetic proximity. These MR effects have been further investigated by Nakayama et al 11 and they found and explained a new magnetoresistance, called spin-Hall magnetoresistance (SMR).…”
Section: Introductionmentioning
confidence: 99%
“…We can model this situation by contacting the spin chain either at the two ends or at some intermediate site. The former configuration corresponds to the "longitudinal" spin Seebeck effect [36][37][38][39][40][41], while the latter one is referred to as "transverse" [35,[42][43][44][45][46] or "nonlocal" [47]. The spin dynamics at the interface pumps a spin current into the contact at site n given by…”
Section: Spin Pumping and Spin Seebeck Effectsmentioning
confidence: 99%